Transformasi Pemahaman Al-Qur’an: Sejarah, I’jaz, dan Dinamika Model Tafsir dalam Studi Islam Kontemporer - Oliviani Salsabila; Ahza Mayla Khoiri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This study is motivated by the importance of understanding the Qur’an as a holy book possessing various aspects of inimitability, including its linguistic, structural, and thematic contents. This study aims to examine the miraculous aspects of the Qur’an, particularly from the perspective of its numerical features and authenticity, as well as to analyze the themes of monotheism (tawhid), law, and social issues as broad objects of exegesis (tafsir). The method employed is qualitative research utilizing a library research approach, conducted through the analysis of relevant exegesis literature and scholarly sources. The results indicate that the Qur’an possesses a unique structural balance and thematic consistency that demonstrate the perfection of divine revelation. The examined religious and social themes are also universal and highly relevant to contemporary life. The implication of this study emphasizes the importance of a comprehensive understanding of the Qur’an, encompassing not only textual aspects but also its context and structure, to strengthen faith and broaden Islamic scholarly insight.